The impact of political thinking on the decision maker in analyzing the strategic environment of the state (applied study in the Iraqi Ministry of Finance) - مهدي, ايناس ضياء (Journal of Economics and Administrative Sciences, 2011)
The Political Thinking Regarded as an important element for the formulation of the stat, weather in its formation, the structure of it s entity, its political system and it s governmental instruments .The political thinking can not act without determined strategy, So they intend to work hard to formulate a railed strategy that make them able to determine its  directions to general issues.   The Study aimed to solve the problem through the following question:1- What are the levels of Political Thinking and Strategic Analysis in the financial ministry?2- What are the relation ship between the dimensions of Political  Thinking and the stages of Strategic Analysis ?3- what is the influence of the  dimensions  of Political  Thinking and Strategic Analysis in the financial ministry?4- What are the differences among the financial ministry partiers in the  dimensions  of Political  Thinking and Strategic Analysis? The executive managers of the  financial ministry regarded as a sample for the research .The questionnaire used to collect  the necessary data the research needs. That data has been analyzed by statistical methods , and proved the rightful of the supposed model.